Gaya Kolonial pada Rumah Tinggal Keluarga Ko Som Ien dan Ko Kwat Ie di Magelang - Matthew Albert Lee Setiawan; Adi Santosa (Intra, 2013)
Magelang is a small town in Central Java which rich in cultural heritage, one of them is colonial buildings. In the early XIX century, Ko Som Ien was a landlord and Ko Kwat Ie was an owner of a cigar factory in Magelang. Their family residentials are exist until now and still keep their originality. This research paper aims to determine the effect of the colonial-style in Ko Som Ien and Ko Kwat Ie Family Residential's Interior at Magelang, using qualitative descriptive research method. The object of the research focused on aspects of the form in which the scope of the research are organization of space, interior structural elements, and transitional elements. The results showed that Ko Som Ien and Ko Kwat Ie Family Residential's Interior at Magelang has influences from more than one Colonial style.